Effects of soil structure on the permeability of saturated Maryland clay. Issue 1 (23rd March 2018) - Yuan, S. Y.; Liu, X. F.; Buzzi, O.
Abstract : This study focuses on the permeability of saturated Maryland clay, a natural expansive soil that can be found close to the University of Newcastle, Australia. Previous studies on this material conducted by the authors have shown that significant microstructural changes occur upon changes of net stress or suction. Consequently, significant variation of permeability can be expected during permeability tests while the soil is in the saturated range. Three series of permeability tests were conducted on statically compacted, dynamically compacted and reconstituted specimens. Two test methods, with different stress paths, were used and the permeability tests were complemented by microstructural investigations. The paper presents a comprehensive multi-scale database of permeability values of a reactive soil possessing different microstructures. Results were expressed as a function of some microstructural descriptors and clear correlations were found between some descriptors and permeability values. However, the results also suggest a strong tortuosity effect, which cannot be directly captured by porosimetry.